Resiliensi Matematis Siswa SMP pada Pembelajaran Matematika Secara Daring - Aisyah Nuraini; Dori Lukman Hakim (Program Studi Pendidikan Matematika, 2023)
A positive attitude towards learning mathematics is crucial and should be present in students as it can reduce the obstacles faced during the learning process. The Covid-19 pandemic has changed all aspects, including education. Teachers and students are required to conduct learning activities online, which of course, affects the mathematical resilience of students. Therefore, the purpose of this article is to describe the mathematical resilience of junior high school students in learning mathematics online. The method used in this article is descriptive qualitative with a non-test instrument in the form of a 30-item questionnaire that can be responded to by students using a Likert scale with a range of 1 to 5 points. The subjects were taken from grade IX students at one of the junior high schools in Karawang Regency. From the analysis that has been conducted, students are still able to overcome technical obstacles during the learning process. However, students face challenges in understanding and the lack of innovation from teachers in delivering material, which only relies on textbooks, so there needs to be development in terms of learning models and the form of the material presented.